PENGGUNAAN BAHAN ACUAN BERSERTIFIKAT OYSTER TISSUE 1566b SEBAGAI INTERNAL QUALITY CONTROL UNTUK MENENTUKAN KADAR TIMBAL TOTAL DALAM TEPUNG IKAN MARLIN DENGAN ELECTROTHERMAL ATOMIC ABSORPTION SPECTROMETRY - Willy Cahya Nugraha; Yohanes Susanto Ridwan (Jurnal Kimia Terapan Indonesia, 2015)
Lead is widely knows as one of the harmful pollutants for humans. Contaminated fishery built by lead may endanger the consumption body. Therefore, contamination monitoring for the fishery products is necessary to be conducted. To ensure the validity of data, Oyster Tissue 1566b certified reference material was used as Internal Quality Control. Marlin fish powder and certified reference materials were analyzed with the same method, personnel, duration or time, equipment and environmental conditions. As the results, it was found that the lead contained in CRM was 0.306 mg.kg-1 with 11.9 % rsd, which is within range of lead content inÂ  the certificate. The method was applied for Marlin Fish. Lead content obtained in this study (1.821 mg.kg-1 with 11.06 % rsd) can be reported with high level of confidence.Keywords: Lead, Certified Reference Materials, Marlin fish